2021
DOI: 10.3389/fonc.2021.665617
|View full text |Cite
|
Sign up to set email alerts
|

Post-Diagnostic Beta Blocker Use and Prognosis of Ovarian Cancer: A Systematic Review and Meta-Analysis of 11 Cohort Studies With 20,274 Patients

Abstract: ObjectivesPrevious experimental studies have indicated that exposure to beta blocker provides protective effects against ovarian cancer (OC). However, findings from epidemiologic studies have still been controversial. Therefore, we carried out a meta-analysis to update and quantify the correlation between post-diagnostic beta blocker usage and OC prognosis.MethodsThe meta-analysis had been registered at PROSPEPO. The number of registration is CRD42020188806. A comprehensive search of available literatures in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…We found that the use of both ACE inhibitors and ARBs during first year after diagnosis had a significantly greater benefit on survival compared to each medication class alone, although the result was based on few outcomes. The possible mechanisms underlying the observed reduction of cancer-specific death risk following the ARB and ACE inhibitors medication use include reduction of inflammation, tumour angiogenesis, invasion and peritoneal dissemination in human ovarian cancer cells by blockage of angiotensin receptors (both Angiotensin II type 1 receptor (AT1R) and Angiotensin II type 2 receptor (AT2R)) [ 6 , 12 ]. According to Suganuma et al, AT1R expression has been observed in 85% of invasive ovarian carcinomas, whereas it was not detected on surface epithelium of the normal ovary [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that the use of both ACE inhibitors and ARBs during first year after diagnosis had a significantly greater benefit on survival compared to each medication class alone, although the result was based on few outcomes. The possible mechanisms underlying the observed reduction of cancer-specific death risk following the ARB and ACE inhibitors medication use include reduction of inflammation, tumour angiogenesis, invasion and peritoneal dissemination in human ovarian cancer cells by blockage of angiotensin receptors (both Angiotensin II type 1 receptor (AT1R) and Angiotensin II type 2 receptor (AT2R)) [ 6 , 12 ]. According to Suganuma et al, AT1R expression has been observed in 85% of invasive ovarian carcinomas, whereas it was not detected on surface epithelium of the normal ovary [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies analysing the association between the use of BBs and survival among ovarian cancer patients report contradictory results. In most studies BBs users showed no association [ 6 , 7 , 9 , 12 , 13 ] or better survival outcomes [ 10 , 25 , 26 ]. A study by Harding et al (2018) found ovarian cancer-specific mortality to be lower among women who used nonselective BBs, but not in selective BBs users [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of beta-blockers on breast, ovarian, colorectal and pancreatic cancer has been investigated in observational studies ( Wen et al, 2021 ). In studies, propranolol has been shown to inhibit cell proliferation, and the combination of propranolol, docetaxel and doxorubicin in the treatment of various soft tissue sarcomas resulted in a better response to treatment, the most sensitive were angiosarcoma and liposarcoma ( Porcelli et al, 2020 ).…”
Section: Propranolol–an Old Drug With New Propertiesmentioning
confidence: 99%